Comparison of brain atrophy in patients with multiple sclerosis treated with first‐ versus second‐generation disease modifying therapy without clinical relapse. (25th June 2020) - Masuda, H.; Mori, M.; Hirano, S.; Uzawa, A.; Uchida, T.; Ohtani, R.; Aoki, R.; Kuwabara, S.
Abstract : Background and purpose: The silent progression of patients with multiple sclerosis (MS) has been reported. The aim of this study was to investigate the association between brain atrophy rates and disease‐modifying drugs (DMDs) in patients with MS during their relapse‐free period. Methods: Patients with relapsing‐remitting MS were classified into two groups on the basis of clinical records, i.e. a first‐generation DMD group treated with interferon‐beta‐1a, interferon‐beta‐1b or glatiramer acetate and a second‐generation DMD group treated with dimethyl fumarate, fingolimod or natalizumab. Brain volume was calculated with SPM12. Results: A total of 45 patients with relapsing‐remitting MS were enrolled in the first‐generation ( n = 22) or second‐generation ( n = 23) DMD group. The annualized relapse rate was lower in the first‐generation than in the second‐generation DMD group (median 0.26 vs. 0.59; P < 0.001). The annualized atrophy rate of the normalized brain volume was not different between the first‐ and second‐generation DMD groups after analysis of covariance (median 0.13% vs. 0.59%; P = 0.17). Conclusions: The median annualized atrophy rate of normalized brain volume in the first‐generation DMD group was similar to the previously reported annual brain atrophy rate of healthy controls, which may suggest that treatment with a first‐generation DMD need not be changed when patients with MS are clinically inactive.